Different oxidation treatments on polystyrene (PS) microspheres by using an ultraviolet/ozone (UVO3) system - Arifin, Mohd Azmir; Mel, Maizirwan; Samsudin, Nurhusna; Hashim, Yumi Zuhanis Has-Yun; Hamzah, Mohd. Salleh; Iis, Sopyan (Pakistan Academy of Sciences, 2017)
Oxidation is a common physical treatment used to render the surface of polystyrene suitable for cell adhesion and spreading. In this work, the effects of oxidation of polystyrene (PS) microspheres by three different treatments; oxidation by ozone aeration only, UV irradiation only or by the combination of both (UVO3), by using a self-fabricated UVO3 system were investigated. Results expressed in carboxylic acid (COOH) concentrations on the surface of microspheres revealed that, the treatment by UVO3 yielded the highest concentration. Presence of atomic oxygen species in UVO3 treatment has contributed to higher COOH concentration.